Heterose e capacidade de combinação em trigo envolvendo fontes de genes de nanismo - Capelin, Marcio Andrei (2014)
The introduction of Rht genes, mainly from breeding programs in Asia, Europe, United States and Mexico has allowed the advancement of wheat (Triticum aestivum L.) to marginal areas considered. In this context, this study aims to evaluate the combining ability, heterosis and heterosis in a 8x8 diallel order to verify the pleiotropic effect (single gene controls several features of the phenotype), in other words, beyond the stature which components of income that are being changed when taller cultivars are crossed with dwarf lines CD 0827, CD 0985 and UTF 0605 provided by national wheat breeding programs. The experiment was conducted in Pato Branco - PR in the 2012 harvest, in a randomized block design with three replications. Hybridizations were performed with eight parents, three of them dwarfs (CD 0827 , CD 0985 and UTF 0605), BRS Pardela, Safira , BRS Tangara, CD 111 and CD 108. The values of the mean squares for GCA were higher than SCA for all traits indicating higher contribution of additive genetic effects. The general combining ability of the dwarf lines (CD 0827 , CD 0985 and UTF 0605) indicated the greatest contributions to the reduction of plant height in both generations evaluated, highlighting the UTF 0605 lineage. The CGC also indicates that UTF 0605, Safira and BRS Tangará parents maximize the number of fertile tillers per plant (NFPP) and CD 0985 , CD 111 were effective in increasing the number of grains per spike (NGS). The Safira, BRS Tangará, CD 108 and CD 0827 between dwarf parents stood out with the highest values for GCA for grain yield per plant (GYP) . The dwarf parents UTF 0605, CD 0985 and CD 0827 are promising sources of additive genes for the development of progenies of lower plant height and increased number of fertile tillers per plant, grains per spike and thousand grain weight. The CD 0827 x Safira, UTF 0605 x Safira, CD 0985 x CD 111, CD 0985 x CD 108, UTF 0605 x CD 111, UTF 0605 x BRS Tangará stood out with higher values of specific combining ability for grain yield, and the first two were higher when considering the values of heterosis and heterosis and inbreeding depression. The results of this study demonstrate the feasibility of using plant population used in breeding programs.